Maternal microchimerism: foreign friend, hidden enemy - Nikola Malinská; Ilja Stříž; Jan Černý (Clinical Science, 2026)
Abstract Maternal microchimerism (MMc) encompasses the transfer and long-term persistence of maternal cells within the offspring—beginning in utero via the placenta and continuing after birth through breastfeeding. Once viewed as an immunological oddity, MMc is now recognized as a dynamic, multifaceted process that permeates the entire field of developmental physiology. Maternal cells, including tissue-specific, immune, and stem/progenitor populations, are not mere passengers; they integrate and functionally engage within fetal and neonatal tissues. Remarkably, MMc brings both protection and risk: supporting immune maturation, defense against infection, and even compensating for immunodeficiencies, while also contributing to the pathogenesis of autoimmune and inflammatory diseases in vulnerable hosts. Additionally, MMc may be involved also in modulation of the tolerance/rejection balance in transplant patients. In the present review, we synthesize the mechanisms of MMc establishment, compare the fetal and neonatal (breast milk-mediated) routes, and critically evaluate its effects across organ systems. Special focus is given to breast milk as a source of diverse maternal cells with complex physiological impacts extending into adulthood, positioning MMc as a true double-edged legacy in mammalian biology.